Genomic or Non-Genomic? A Question about the Pleiotropic Roles of Vitamin D in Inflammatory-Based Diseases - Holick, Michael F. (2023)
Vitamin D (vit D) is widely known for its role in calcium metabolism and its importance for the bone system. However, various studies have revealed a myriad of extra-skeletal functions, including cell differentiation and proliferation, antibacterial, antioxidant, immunomodulatory, and anti-inflammatory properties in various cells and tissues. Vit D mediates its function via regulation of gene expression by binding to its receptor (VDR) which is expressed in almost all cells within the body. This review summarizes the pleiotropic effects of vit D, emphasizing its anti-inflammatory effect on different organ systems. It also provides a comprehensive overview of the genetic and epigenetic effects of vit D and VDR on the expression of genes pertaining to immunity and anti-inflammation. We speculate that in the context of inflammation, vit D and its receptor VDR might fulfill their roles as gene regulators through not only direct gene regulation but also through epigenetic mechanisms.